Histopathological changes in the lungs from dogs with tick paralysis: 25 cases (2010–2012). Issue 8 (26th July 2013) - Webster, RA; Mackie, JT; Haskins, SC
<x xml:space="preserve">Abstract</x> Objective To determine the prevalence and nature of histological lung lesions in dogs with tick paralysis. Methods A prospective study of 25 client‐owned dogs that died during treatment for tick paralysis or were euthanased because of either the severity of the disease process or financial constraints was conducted at a veterinary emergency hospital in Queensland, Australia. Lung specimens were collected postmortem for histopathological examination. Results All 25 dogs had significant pulmonary changes: 9 exhibited congestion and alveolar oedema, with no obvious inflammatory cell infiltrate; 1 exhibited a mild increase in the number of alveolar macrophages in addition to congestion and alveolar oedema; the remaining 15 dogs had moderate or severe bronchopneumonia, with 2 showing evidence of aspiration pneumonia. Conclusion Dogs with clinically severe tick paralysis are likely to have pulmonary parenchymal disease. Bronchopneumonia may be present in a significant proportion of cases and may reflect aspiration.